Deliberating and Learning Contentious Issues: How Divided Societies Represent Conflict in History Textbooks. (December 2013) - Drake, Anna; McCulloch, Allison
Abstract History education can either exacerbate polarization and division or it can have conciliatory potential. Looking at a number of divided societies, we identify trends in curriculum portrayals of inter‐group conflict. Noting the power of re‐telling the past, we argue for a conciliatory approach to textbook design that entails the inclusion of multiple narratives. We detail why groups need to set out their own account of events and discuss the importance of the way that groups develop their accounts. We recommend an institutional, process‐based approach to textbook design grounded in the values of deliberative consociationalism and argue that the conciliatory approach is best pursued in a two‐stage model of deliberations. We develop this model and focus on how deliberations might occur and with what restrictions, taking seriously concerns about the applicability of deliberation in divided societies.